2010
DOI: 10.1007/s11426-010-0125-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-carbazole derivatives for two-photon absorption data storage: Synthesis, optical properties and theoretical calculation

Abstract: BCPBC), with different conjugated arms, have been designed and synthesized. Their one-and two-photon absorption (TPA) and excited fluorescence properties have been experimentally investigated. The two-photon absorption cross-sections of two compounds were estimated by two-photon excited fluorescence technique using 200 fs, 76 MHz, Ti:sapphire laser, which are 22 and 154 GM for BCSPC and BCPBC, respectively. The optimal excitation wavelengths are 780 nm for both BCSPC and BCPBC. A data recording experiment prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…Intensive efforts are continuously produced in the development of novel experimental approaches as well as new materials suitable for the next generations of optical storage devices. Two-photon processes are interesting, as they exhibit a quadratic dependence on the incident light intensity, thus providing a confined recording and, as a result, a high storage capacity . In the present work, we have designed a class of materials allowing an unprecedented complete and straightforward second-harmonic generation (SHG)-assisted writing−reading−erasing−writing sequence with a high contrast, a process that is particularly appealing for optical data storage applications.…”
mentioning
confidence: 99%
“…Intensive efforts are continuously produced in the development of novel experimental approaches as well as new materials suitable for the next generations of optical storage devices. Two-photon processes are interesting, as they exhibit a quadratic dependence on the incident light intensity, thus providing a confined recording and, as a result, a high storage capacity . In the present work, we have designed a class of materials allowing an unprecedented complete and straightforward second-harmonic generation (SHG)-assisted writing−reading−erasing−writing sequence with a high contrast, a process that is particularly appealing for optical data storage applications.…”
mentioning
confidence: 99%
“…Confocal uorescence microscopy conrmed that 92 could be used for monitoring Zn 2+ in living cells. Other simple dppz possessing phen based uorescent chemosensors (96 and 97), 154,155 differing only by the presence/ absence of phenyl ring recognized Hg 2+ and Zn 2+ ions, respectively in DMF buffered solution. The chemosensor 96 gave enhanced uorescence with addition of Hg 2+ ions, attributed to the formation of the 96-Hg 2+ complex with a stability constant of 3.7 Â 10 5 M À1 .…”
Section: Cationsmentioning
confidence: 99%
“…Two-photon absorption (2PA) was predicted in the 1930s by Maria Göppert-Mayer, and nowadays, one witnesses its numerous applications including biological imaging, , photodynamic therapy, , three-dimensional (3D) microfabrication, and 3D optical data storage. , With these applications in mind, there is ongoing research regarding the development of two-photon and three-photon absorbers. , Based on structure–property relationships, it has been observed that significant 2PA cross sections can be achieved in systems that exhibit some of these characteristics such as noncentrosymmetry, , planarity, donor–acceptor interactions, or extended π-conjugation. Studies have revealed that planarity in the π-conjugated system leads to better π-orbital overlap, which is beneficial for nonlinear absorption cross sections corresponding to transitions to low-lying states as it facilitates charge transfer upon electronic excitation. Fang et al studied the 2PA activity of p -triphenyl-based dendrimer systems, and it was observed that the planar form exhibited enhanced 2PA .…”
Section: Introductionmentioning
confidence: 99%
“…Two-photon absorption (2PA) was predicted in the 1930s by Maria Göppert-Mayer, and nowadays, one witnesses its numerous applications including biological imaging, 1 , 2 photodynamic therapy, 3 , 4 three-dimensional (3D) microfabrication, 5 and 3D optical data storage. 6 , 7 With these applications in mind, there is ongoing research regarding the development of two-photon 8 10 and three-photon absorbers. 11 , 12 Based on structure–property relationships, it has been observed that significant 2PA cross sections can be achieved in systems that exhibit some of these characteristics such as noncentrosymmetry, 13 , 14 planarity, 15 17 donor–acceptor interactions, 18 23 or extended π-conjugation.…”
Section: Introductionmentioning
confidence: 99%